Study of the Structure and the Dynamics of Ge-Sb-Te Liquids - Dorin, Thomas (My University, 2010)
Some liquids Ge-Te, such as the eutectic alloy Ge15Te85, exhibit a decrease of their volume when the temperature increases just above their melting point. This negative thermal expansion (NTE) is accompanied with thermodynamic anomalies and important changes in the electrical conductivity. Simulations have shown that this NTE is associated with a distortion of the octahedral structure around Ge atoms. Conversely, it was shown that liquid Ge15Sb85 does not exhibit any anomaly. This thesis focused on the effect of substituting Sb to Te in Ge15Te85. The total structure factors were measured by neutron scattering on the 7C2 spectrometer at the LLB (Laboratory Léon Brillouin, Saclay). The analysis of the results from this experiment suggested that Sb does not kill off the anomaly. Indeed, when Sb is added to Ge15Te85, the melting temperature of the alloy is increased. As a result, the anomaly that could be seen in the liquid for Ge15Te85, is moved into the overcooled area for Ge15(SbxTe1- x)85 alloys with 0<x<0.5 but what happens for alloys with x>0.5 remains uncertain. The dynamics of liquid Ge15Te85 were measured by Inelastic X-Ray scattering on the ID28 beamline at the ESRF (Grenoble). The containment for the sample had to be invented for this experiment. In the ternary Ge-Te-Sb phase diagram, some alloys are the subject of numerous studies, they are known as phase change materials. Those materials exhibit a rapid and reversible phase transition between an amorphous and a crystalline phase with different electronic properties. The anomaly in the liquid state and the transition in the PCM are both associated with important changes in the electronic properties. The relation between those transitions is discussed.
Keywords: Materialvetenskap; Materialteknik; Funktionella material; Övrig teknisk fysik; Materials Science; Materials Engineering; Functional materials; Other engineering physics